'Boxing in the corner': A modified retrograde approach for the management of proximal ureteric stones of 1–2 cm. Issue 2 (3rd April 2021) - Elgebaly, Omar Farid; Abdeldaeim, Hussein; Abouyoussif, Tamer; Fahmy, Ahmed Mahmoud; Edris, Faisal; Zahran, Abdelrahman; Assem, Akram
ABSTRACT: Objectives : To study a modification to the conventional retrograde ureteroscopic approach for treating proximal ureteric stones of 1–2 cm; we intentionally push the stone from the proximal ureter into a favourable calyx then the flexible ureteroscope is used to fragment the trapped stone using laser lithotripsy ('boxing in the corner'). Patients and methods : The study was conducted in a randomised prospective manner and included 100 patients who presented with a single proximal ureteric stone of 1–2 cm. We randomised the patients into two equal groups: Group A (50 patients) underwent the conventional retrograde technique (CRT) and Group B (50 patients) underwent the modified retrograde technique (MRT) with the primary intention of relocating the stone into a favourable calyx. Intended relocation of the proximal ureteric stone in the MRT group was achieved in a stepwise manner. All intraoperative parameters and postoperative outcomes were recorded and compared between the two groups. Results : There was no statistical significant difference in terms of the patients' demographics and stone criteria between the two groups. The stone-free rate (SFR) was significantly higher in Group B (92%) compared to Group A (78%) ( P = 0.049). Fluoroscopy time was significantly longer in Group B ( P < 0.001), while operative time, lithotripsy time and hospital stay were comparable. There was no difference between the groups regarding complications. Conclusion : The MRT was found to be safe and more effective than the CRT for treating proximal ureteric stones of 1–2 cm, with a significantly higher SFR. Abbreviations CONSORT: Consolidated Standards of Reporting Trials; ESWL: extracorporeal shockwave lithotripsy; fURS: flexible ureteroscope; NCCT: non-contrast CT; SFR: stone-free rate; YAG: yttrium-aluminium-garnet